2013
DOI: 10.1021/ie402360f
|View full text |Cite
|
Sign up to set email alerts
|

Modification Strategies for Carbon Nanotubes as a Drug Delivery System

Abstract: Carbon nanotubes (CNTs) are extensively explored in materials science due to their unique structure and consequent mystical properties. CNTs are enjoying increasing popularity as building blocks for novel drug delivery systems as well as for bioimaging and biosensing. The recent strategies to functionalize CNTs have resulted in the generation of biocompatible and water-soluble CNTs that are well suited for high treatment efficacy and minimum side effects for future cancer therapies with low drug doses. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…The high off-target toxicity of classic cancer chemotherapeutics, coupled with their general lack of tumor localizing capability and, in some instances, poor solubility or stability profiles has prompted considerable effort to develop so-called drug delivery systems (DDS) 9 that might overcome some or all of these deficiencies. Promising approaches include the use of liposomes, 10 vesicles, 11 nanoparticles, 12 hydrogels, 13 carbon nanotubes, 14 metal–organic frameworks, 15 and supramolecular organic frameworks. 16 Several of these systems are “smart” enough to realize the controllable release in response to environmental changes (pH, temperature and enzyme, etc. )…”
Section: Introductionmentioning
confidence: 99%
“…The high off-target toxicity of classic cancer chemotherapeutics, coupled with their general lack of tumor localizing capability and, in some instances, poor solubility or stability profiles has prompted considerable effort to develop so-called drug delivery systems (DDS) 9 that might overcome some or all of these deficiencies. Promising approaches include the use of liposomes, 10 vesicles, 11 nanoparticles, 12 hydrogels, 13 carbon nanotubes, 14 metal–organic frameworks, 15 and supramolecular organic frameworks. 16 Several of these systems are “smart” enough to realize the controllable release in response to environmental changes (pH, temperature and enzyme, etc. )…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that CNTs support the growth of osteoblastic cells by stimulating the production of extracellular matrix (ECM), a central step during the formation of bone tissue . Furthermore, CNTs could be a more effective drug delivery carrier due to their external functionalizable surface and their hollowed cavity that can encapsulate several bioactive molecules …”
Section: Discussionmentioning
confidence: 99%
“…These are isotropic mixtures of oils, hydrophobic surfactant and sometimes contains co-solvents upon gentle agitation or digestive motility at a great rate produces fine o/w emulsion. [19] Others: Carbon nanotubes: These are gaining popularity as novel drug delivery systems as well as for biosensing. This resulted in production of biocompatible nanotubes with minimal side effects.…”
Section: Carrier Associated With Lymphatic Deliverymentioning
confidence: 99%